Workers' compensation : analysis for its second century - Hunt, H. Allan; Dillender, Marcus (WE focus series., 2017)
"H. Allan Hunt and Marcus Dillender provide a succinct analysis of the state of WC programs in North America by focusing on three key performance issues: 1) the adequacy of compensation for those disabled in the workplace, 2) return-to-work performance for injured workers, and 3) prevention of disabling injury and disease. Following a brief introductory chapter that provides a discussion of the difficulties of trying to compare so many diverse programs, Hunt and Dillender devote a chapter to each of the three performance issues and provide empirical findings and useful guidance for policymakers"--Publisher's description.